An in vitro investigation of water sorption and solubility of two acetal denture base materials. - (:unkn) unknown (My University, 2005)
Acetal resins have been used as an alternative denture base and clasp material recently. The aim of this study was to compare water sorption and water solubility of pink and white acetal resins as compared to a heat-polymerized polymethyl methacrylate resin (PMMA). The tests were performed in accordance with International Standards Organization specification No: 1567. Pink acetal resin showed significantly lower water sorption than heat-polymerized acrylic resin and white acetal resin. PMMA showed significantly higher solubility than pink and white acetal resin. Water sorption and solubility of PMMA, pink and white acetal resins were within the ISO specification limit.